Freezing Tolerance‐Associated Quantitative Trait Loci in the Brundage × Coda Wheat Recombinant Inbred Line Population. Issue 3 (1st May 2014) - Case, Austin J.; Skinner, Daniel Z.; Garland‐Campbell, Kimberly A.; Carter, Arron H.
ABSTRACT: Freezing tolerance is an essential trait for winter wheat cultivars. A genetic analysis of a Brundage × Coda winter wheat recombinant inbred line (RIL) mapping population was undertaken to identify quantitative trait loci (QTL) associated with freezing tolerance. Five‐week to 6‐wk old, cold‐acclimated plants were frozen to –10.5, –11.5, or –12.5°C. The standardized mean percentage survival of all RILs within each temperature was 61, 44, and 28%, respectively. A total of 2391 polymorphic DNA markers including 1984 single nucleotide polymorphism (SNP), 232 Diversity Array Technology (DArT), and 175 simple sequence repeat (SSR) markers were used to create a genome‐wide genetic linkage map. The QTL analysis identified six QTL that were associated with freezing tolerance at either a specific temperature or a combination of temperatures. The QTL QFrbr.wak‐5A was associated with freezing tolerance at all temperatures tested and was on chromosome 5AL. Further marker analysis indicates that this QTL is not an effect of known sequence polymorphisms at Vrn‐A1 . On the basis of map homology, QFrbr.wak‐5A mapped at or near the CBF (cold binding factor) gene cluster at Fr‐A2, but not an effect of TaCBF‐A15, TaCBF‐A14, or TaCBF‐A12 . Other QTL were located on chromosomes 2A, 3A, 5B, and 6D, and were significant at only specific temperatures. Identification of QTL associated with freezing tolerance may lead to useful genetic markers for marker‐assisted selection, allowing for more efficient development of freezing tolerant cultivars. Additional studies of this QTL will further enhance knowledge of cold tolerance in wheat, as this QTL is not due to known sequence variation at Vrn‐A1 or tested CBF genes.